2021
DOI: 10.1108/jima-09-2020-0277
|View full text |Cite
|
Sign up to set email alerts
|

The prerequisites and consequences of customers’ online experience regarding the moderating role of brand congruity: evidence from an Iranian bank

Abstract: Purpose The purpose of this paper is to investigate the prerequisites of customer online experience and its outcomes in banks. Brand congruity is an important mediating variable in these connections. Design/methodology/approach A quantitative approach is used to test the model based on the literature review. The subjects are online customers of an Iranian bank, Bank Mellat, in East Azerbaijan Province, which is famous for its e-banking. Data analysis was conducted using structural equation modeling. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 133 publications
1
6
0
Order By: Relevance
“…This is in line with the research from (Omoregie et al, 2019), which states that corporate image will have an impact on customer satisfaction, and afterwards customer satisfaction will affect customer loyalty. The same finding was confirmed in research in Iran conducted by (Ashrafpour et al, 2021). It is stated that service quality is moderated by customer experience before affecting customer satisfaction and loyalty.…”
Section: Hypothesis Testing Resultssupporting
confidence: 68%
“…This is in line with the research from (Omoregie et al, 2019), which states that corporate image will have an impact on customer satisfaction, and afterwards customer satisfaction will affect customer loyalty. The same finding was confirmed in research in Iran conducted by (Ashrafpour et al, 2021). It is stated that service quality is moderated by customer experience before affecting customer satisfaction and loyalty.…”
Section: Hypothesis Testing Resultssupporting
confidence: 68%
“…Banks have been a frontrunner in upgrading functional aspects, the most recent being chatbots (Trivedi, 2019). The functional aspects of a banking website shall include ease of access, commitment and full responsiveness of the Web page (Ashrafpour et al , 2021). Studies found a positive relationship between functional quality, CE, satisfaction and loyalty (Mbama and Ezepue, 2018; Amin, 2016) in the UK and Malaysian banking.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In another study, Shaikh et al (2020) emphasised customer awareness, perceived usefulness and perceived ease of use as CE antecedents of mobile app-based banking. Ashrafpour et al (2021) examined CE based on affective dimension (usability and hedonic experience) and functional dimension (sociability and practical experience) applied to Islamic banking in Iran. Recent literature in the marketing-related field puts forth the impact of adding game-like features to the Web portal (Huotari and Hamari, 2012; Rodrigues et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Soetan et al(2021) reported service maintenance, service technology and service dynamics as significant factors of customer experience. In Iran,Ashrafpour et al (2021) reported affective and functional experience as the signif icant components of customer experience. Thus, service quality & system quality are the significant factors as they were shown to have positive impact on online bank customers.Mokhlis et al (2018) stated ATM (automated teller machine) is one of the most used banking services.…”
mentioning
confidence: 99%